Method for producing positive electrode active material for lithium secondary battery and positive electrode active material for lithium secondary battery produced thereby

By using carbon materials with hollow structures to mechanically treat lithium transition metal oxides, a uniform carbon coating is formed, which solves the problem of oxidation number change in the positive electrode active material of lithium secondary battery during high-temperature heat treatment, and improves the conductivity and lifespan characteristics.

CN114846650BActive Publication Date: 2025-02-11LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180007427.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-30
Filing Date
2021-01-29
Publication Date
2025-02-11
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

The positive electrode active materials of existing lithium secondary batteries are prone to change in surface oxidation number during high-temperature heat treatment, affecting the conductivity and life characteristics.

Method used

Carbon materials with hollow structures are surface treated with lithium transition metal oxides through mechanical means to form a uniform carbon coating to improve conductivity and life characteristics.

Benefits of technology

Without changing the lithium transition metal oxide structure, a thin and uniform carbon coating is formed, which improves the conductivity of the positive electrode active material and extends the input/output characteristics and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114846650B_ABST
    Figure CN114846650B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a positive electrode active material, a positive electrode active material manufactured by the method, a positive electrode containing the positive electrode active material, and a lithium secondary battery. The method comprises: mixing a lithium transition metal oxide and a hollow carbon material to form a mixture; and mechanically treating the mixture to form a carbon coating on the surface of the lithium transition metal oxide, wherein the hollow carbon material is in a chain shape and has a carbon content of 500 m / s. 2 / g or more, a specific surface area of ​​1.0 or more, a degree of graphitization (I D / I G ) and DBP oil absorption above 300mL / 100g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0011338 filed on January 30, 2020, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to a method for manufacturing a positive electrode active material for a lithium secondary battery, a positive electrode active material manufactured by the manufacturing method, a positive electrode for a lithium secondary battery containing the positive electrode active material, and a lithium secondary battery. Background Art

[0005] As the technology of mobile devices develops and the demand increases, the demand for secondary batteries as energy sources is rapidly increasing. Among these secondary batteries, lithium secondary batteries with high energy density and high voltage, long cycle life and low self-discharge rate have been commercialized and widely used.

[0006] Lithium transition metal oxides have been used as positive electrode active materials for lithium secondary batteries. Among these lithium transition metal oxides, lithium-cobalt oxides such as LiCoO2 with high operating voltage and excellent capacity characteristics are mainly used. However, due to the unstable crystal structure caused by delithiation, LiCoO2 has very poor thermal properties and is also expensive. Therefore, there are limitations in using a large amount of LiCoO2 as a power source for fields such as electric vehicles.

[0007] As a material to replace LiCoO2, lithium manganese composite metal oxides (LiMnO2, LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.) or lithium nickel composite metal oxides (LiNiO2, etc.) have been developed. Among the above materials, lithium nickel composite metal oxides, which have a high reversible capacity of about 200mAh / g and are easy to realize high-capacity batteries, have been actively studied and developed. However, when compared with LiCoO2, LiNiO2 has lower thermal stability, and there is a problem in that when an internal short circuit occurs in a charged state due to external pressure, etc., the positive electrode active material itself decomposes, causing the battery to rupture and catch fire. Therefore, as a method for improving the low thermal stability of LiNiO2 while maintaining the excellent reversible capacity of LiNiO2, LiNiO2 in which a portion of the nickel is replaced by cobalt has been developed. 1-α Co α O2 (α=0.1 to 0.3) or lithium-nickel-cobalt metal oxide in which a portion of nickel is replaced by Mn, Co or Al.

[0008] However, for lithium-nickel-cobalt metal oxide, due to a sharp rise in the price of cobalt, Co-poor cathode materials containing no cobalt or Ni-rich cathode materials containing excess nickel have been actively studied in terms of cost and energy density.

[0009] On the other hand, compared with the commonly used and excessively used Co-rich composition, the Co-poor positive electrode material or the Ni-rich positive electrode material has the problem that the conductivity of the positive electrode active material is low and it is easy to be affected by moisture. In order to solve the above problems, attempts have been made to form a carbon coating on the surface of the above-mentioned positive electrode material using asphalt or the like. However, in the case of the carbon coating, the disadvantage is that it should be accompanied by a high-temperature heat treatment for carbonization, and when the high-temperature heat treatment is performed, the carbon element on the surface reacts with the oxygen on the surface of the positive electrode material and is reduced, which causes a large change in the oxidation number of the positive electrode material, resulting in degradation of the performance of the positive electrode material.

[0010] Therefore, there is a need to develop a positive electrode active material capable of improving conductivity and life characteristics by forming a thin and uniform carbon coating on the surface of the positive electrode active material without changing the oxidation number of the surface of the positive electrode material caused by a high-temperature heat treatment process. Summary of the invention

[0011] Technical issues

[0012] In order to solve the above problems, the first aspect of the present invention provides a method for manufacturing a positive electrode active material, wherein a lithium transition metal oxide is mechanically surface-treated with a hollow-structured carbon-based material to form a uniform carbon coating on its surface.

[0013] A second aspect of the present invention provides a positive electrode active material manufactured by the above-mentioned manufacturing method, thereby being able to improve conductivity by forming a thin and uniform carbon coating on the surface of the lithium transition metal oxide.

[0014] A third aspect of the present invention provides a positive electrode for a lithium secondary battery comprising the positive electrode active material.

[0015] A fourth aspect of the present invention provides a lithium secondary battery comprising the positive electrode.

[0016] Technical Solution

[0017] According to one aspect of the present invention, a method for manufacturing a positive electrode active material is provided, wherein the method comprises: mixing a lithium transition metal oxide and a hollow structured carbon material to form a mixture; and mechanically surface treating the mixture to form a carbon coating on the surface of the lithium transition metal oxide, wherein the hollow structured carbon material is chain-shaped and has a carbon content of 500 m / s. 2 / g or more, a specific surface area of ​​1.0 or more, a degree of graphitization (I D / I G ) and DBP oil absorption above 300mL / 100g.

[0018] According to another aspect of the present invention, there is provided a positive electrode active material, the positive electrode active material comprising: a lithium transition metal oxide; and a carbon coating formed on the surface of the lithium transition metal oxide, wherein the carbon coating is formed on the surface of the lithium transition metal oxide, the carbon coating has a thickness of 500 nm or less, and the positive electrode active material has a thickness of 0.5 nm or less. 2 / g to 50m 2 / g BET specific surface area.

[0019] According to another aspect of the present invention, there is provided a positive electrode for a lithium secondary battery, the positive electrode for a lithium secondary battery comprising the positive electrode active material.

[0020] According to another aspect of the present invention, a lithium secondary battery is provided. The lithium secondary battery includes the positive electrode for a lithium secondary battery.

[0021] Beneficial Effects

[0022] According to the present invention, when a carbon coating is formed on the surface of a lithium transition metal oxide, the carbon coating is formed by a physical method using a carbon-based material having a hollow structure, so that a thin and uniform carbon coating can be formed without changing the oxidation number of the surface of the positive electrode material. Therefore, the conductivity of the positive electrode active material can be improved, and the gelation of the slurry when the positive electrode is mixed can be prevented, and when the positive electrode active material is applied to a battery, the input / output characteristics, life characteristics, etc. of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image showing a carbon material having a hollow structure used in an embodiment of the present invention;

[0024] Figure 2 is a SEM image showing a carbon material having a dense structure used in a comparative example of the present invention;

[0025] Figure 3 are SEM images showing the surfaces of (a) the positive electrode active material of Comparative Example 2, (b) the positive electrode active material of Comparative Example 1, and (c) the positive electrode active material of Example 1;

[0026] Figure 4 are SEM images showing the surfaces of (a) the positive electrode active material of Comparative Example 2, (b) the positive electrode active material of Comparative Example 4, and (c) the positive electrode active material of Example 1;

[0027] Figure 5 is a SEM image showing the surface of the positive electrode active material manufactured in Example 1;

[0028] Figure 6 is a SEM image showing the surface of the positive electrode active material produced in Comparative Example 6. DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in more detail.

[0030] It will be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It will be further understood that on the basis of the principle that the inventor can appropriately define the meaning of words or terms to best explain the present invention, the words or terms should be interpreted as having the same meaning as their meaning in the relevant technical background and technical concept of the present invention.

[0031] Throughout this specification, "primary particle" refers to a primary structure of a single particle, and "secondary particle" refers to an aggregate of primary particles aggregated through physical or chemical bonding between the primary particles in the absence of an intentional aggregation or assembly process for the primary particles constituting the secondary particles, i.e., a secondary structure.

[0032] Throughout this specification, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77K) using Belsorp-mino II of BEL Japan Co., Ltd.

[0033] Throughout the specification, "dibutyl phthalate (DBP) oil absorption" is a measure of the pores of secondary particles in which primary particles of a carbon-based material are aggregated, and indicates how well the primary particles are connected in the carbon-based material. The DBP oil absorption can be measured by mixing DBP as a plasticizer with a predetermined amount of carbon black to measure the torque change due to the impregnation of the plasticizer. Generally, the greater the DBP oil absorption, the better the conductivity.

[0034] Throughout this specification, "graphitization degree" refers to the degree to which amorphous carbon is partially or completely converted into crystalline graphite, and can be confirmed using Raman spectroscopy. The structure of the carbon material can be analyzed thereby. In the Raman spectrum of a carbon material, the G band is a band representing the sp 2 The D band is the peak of the sp bond, and it indicates a carbon crystal without structural defects. 3 bond peak, and when the sp 2 The atomic bonds forming the bond break and become sp 3When the disorder or defects existing in the carbon-based material are generated, the D band increases, so that the maximum peak intensity (I D ) for the maximum peak intensity of the G band (I G ) ratio (I D / I G ) to quantitatively evaluate the degree of disorder or defects.

[0035] Method for producing positive electrode active material

[0036] The inventors discovered that when a carbon coating is formed on a lithium transition metal oxide, if a carbon material having a specific structure is used to form the carbon coating by a mechanical fusion method, a uniform and thin carbon coating can be formed on its surface without changing the structure of the lithium transition metal oxide, thereby completing the present invention.

[0037] Specifically, the method for manufacturing a positive electrode active material according to the present invention comprises: mixing a lithium transition metal oxide and a hollow structured carbon material to form a mixture; and mechanically treating the mixture to form a carbon coating on the surface of the lithium transition metal oxide, wherein the hollow structured carbon material is in a chain shape and has a carbon content of 500 m / s. 2 / g or more, a specific surface area of ​​1.0 or more, a degree of graphitization (I D / I G ) and DBP oil absorption above 300mL / 100g.

[0038] Hereinafter, the method of manufacturing a positive electrode active material according to the present invention will be described in more detail.

[0039] First, in order to manufacture the positive electrode active material according to the present invention, a lithium transition metal oxide is prepared.

[0040] For example, the lithium transition metal oxide may have a size of 50nm to 4000nm, preferably 50nm to 2000nm. For example, the lithium transition metal oxide may have the form of secondary particles formed by the aggregation of primary particles, or have a single particle form made by the primary particles alone. For example, when the lithium transition metal oxide is formed as a secondary particle formed by the aggregation of primary particles, the energy density per unit volume of the electrode can be increased, and the contact area between the lithium transition metal oxide and the electrolyte is large and the movement distance of lithium ions in the lithium transition metal oxide is short, so that high capacity and high power characteristics can be easily exhibited. For example, when the lithium transition metal oxide is formed in the form of a single particle, the calendering density is increased, so that the structural stability of the battery can be improved.

[0041] Any lithium transition metal oxide commonly used as a positive electrode active material can be used as the lithium transition metal oxide without limitation, as long as the insertion or extraction of lithium ions can easily occur during charge / discharge. For example, the lithium transition metal oxide can be: a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium manganese oxide such as Li 1+y1 Mn 2-y1 O4 (0≤y1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; LiNi 1-y2 M y2 O2 (wherein M is one or more selected from the following: Co, Mn, Al, Cu, Fe, Mg, B and Ga, and 0.01≤y2≤0.3) represented by Ni site type lithium nickel oxide; represented by the formula LiMn 2-y3 M y3 O2 (wherein M is one or more selected from the following: Co, Ni, Fe, Cr, Zn and Ta, and 0.01≤y3≤0.1) or a lithium manganese composite oxide represented by the formula Li2Mn3MO8 (wherein M is one or more selected from the following: Fe, Co, Ni, Cu and Zn); LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions, etc., but is not limited to this.

[0042] Next, the lithium transition metal oxide and the hollow-structured carbon-based material are mixed to form a mixture.

[0043] The carbon-based material is in a chain shape and may be in the form of secondary particles formed by aggregation of primary particles. Since the carbon-based material is in the form of secondary particles formed by aggregation of primary particles, pores may be included inside the carbon-based material.

[0044] The size of the primary particles of the carbon material can be less than 50nm, preferably 5nm to 50nm. When the size of the primary particles of the carbon material meets the above range, it is conducive to forming a uniform coating. In addition, because the carbon material is chain-shaped, even when the size of the primary particles of the carbon material is as small as the above range, a carbon coating can be uniformly formed on the surface of the lithium transition metal oxide.

[0045] For example, when the size of the primary particles of the carbon material is greater than 50 nm, there may be a problem that a completely uniform coating cannot be formed due to partial aggregation of carbon.

[0046] According to the present invention, the specific surface area of ​​the hollow carbon material can be 500m 2 / g or more, preferably 500m2 / g to 2500m 2 / g, at this time, its graphitization degree is 1.0 or more, preferably 1.0 to 2.0, and its DBP oil absorption is 300mL / 100g or more, preferably 300mL / 100g to 2000mL / 100g, and most preferably 300mL / 100g to 1000mL / 100g.

[0047] When the hollow structure carbon material has a BET specific surface area and a degree of graphitization within the above range, it means that the hollow structure carbon material has a low crystallinity. For example, when the BET specific surface area is less than the above range or the degree of graphitization is less than the above range, the carbon material may have a dense structure.

[0048] Specifically, Figure 1 As shown, the carbon-based material of the hollow structure according to the present invention is chain-shaped and exhibits low crystallinity. In this case, because the structure collapses due to the force applied from the outside, when the carbon-based material is used to form a carbon coating, the carbon-based material is crushed and in close contact with the surface of the lithium transition metal oxide due to the force applied from the outside, so that a carbon coating of uniform thickness can be formed on the surface of the secondary particles. In particular, when the lithium transition metal oxide has the form of secondary particles formed by the aggregation of primary particles, a carbon coating can be uniformly formed even at the boundaries between the primary particles. As a result, the conductivity of the positive active material can be improved, and the BET specific surface area of ​​the positive active material finally manufactured can also be maintained at a low level, so that side reactions with the electrolyte caused by the increase in the BET specific surface area can be prevented in advance.

[0049] For example, a carbon-based material having a graphitization degree of less than 1.0 has a high crystallinity, such as Figure 2 As shown, it will not be affected by structural collapse. Therefore, even when a force is applied from the outside, the carbon-based material can be coated while maintaining its crystallinity on the surface of the lithium transition metal oxide without causing the structure of the carbon-based material to collapse, thereby increasing the BET specific surface area. In addition, because the carbon-based material forms a carbon-based coating in the form of adhesion to the surface of the lithium transition metal oxide without structural collapse, it is not easy to form a uniform carbon coating on the surface of the positive electrode active material. In particular, when the lithium transition metal oxide has the form of secondary particles formed by the aggregation of primary particles, it is difficult to form a carbon coating at the boundary between the primary particles of the lithium transition metal oxide, so that it is difficult to form a uniform carbon coating.

[0050] Furthermore, the DBP oil absorption of the carbon-based material according to the present invention is 300 mL / 100 g or more, preferably 300 mL / 100 g to 2000 mL / 100 g.

[0051] In the present invention, "dibutyl phthalate (DBP) oil absorption" is a measure of the pores of the carbon-based material in the form of secondary particles formed by aggregation of primary particles, and indicates how well the primary particles are connected in the carbon-based material. Generally, the larger the DBP oil absorption, the better the connection of the primary particles in the carbon-based material, thereby being able to exhibit improved conductivity.

[0052] For example, when the DBP oil absorption is less than the above range, primary particles in the carbon-based material are not well connected, so that even when a carbon coating layer is formed by the carbon-based material, it is difficult to exhibit improved conductivity.

[0053] The lithium transition metal oxide and the carbon-based material can be mixed by mixing the carbon-based material in an amount of 0.1 to 1.5 parts by weight, preferably 0.1 to 1 parts by weight, relative to 100 parts by weight of the lithium transition metal oxide. When mixed within the above range, a uniform carbon coating can be formed on the entire surface of the lithium transition metal oxide. On the other hand, when the mixing amount of the carbon-based material is greater than the above range, an excessively thick carbon coating will be formed, which will instead become a resistance to the diffusion of lithium ions, so that when applied to a battery, the input / output characteristics of the battery may be deteriorated.

[0054] Next, a carbon coating is formed on the surface of the lithium transition metal oxide by mechanically surface treating the mixture.

[0055] According to the present invention, the mechanical treatment of the mixture can be carried out by mechanical fusion. Specifically, the mechanical fusion method can be carried out under dry process conditions without additional additives such as solvents, adhesives, etc. using a nobilta device. Specifically, the mechanical fusion method can be carried out while stirring the reactor at a current of 3 to 15A, a power of 0.2 to 5.5W, and a rotation speed of 500 to 6000rpm relative to a 0.5L nobilta device at room temperature (20°C). The mechanical fusion method can have different current, power, and rotation speed conditions depending on the capacity of the device. For example, if the capacity of the device increases, the power may increase, but the rotation speed may decrease. Specifically, for example, when a nobilta device with a capacity of 300L is used, the mechanical fusion method can be carried out while stirring at a rotation speed of 50 to 800rpm at a power of 10 to 200W. Because the dispersibility of the particles is improved by the mechanical fusion method, the carbon material can be equally spaced on the surface of the lithium transition metal oxide, so that a uniform carbon coating can be formed on the surface of the lithium transition metal oxide. In addition, even when the lithium transition metal oxide has the form of secondary particles in which primary particles are aggregated, the carbon coating layer may be formed not only on the surface of the secondary particles of the lithium transition metal oxide but also at the boundaries between the primary particles.

[0056] Positive electrode active material

[0057] In addition, the present invention provides a positive electrode active material manufactured by the above method. Specifically, the positive electrode active material comprises: a lithium transition metal oxide; and a carbon coating formed on the surface of the lithium transition metal oxide, wherein the carbon coating is formed on the surface of the lithium transition metal oxide, the carbon coating has a thickness of 500 nm or less, and the positive electrode active material has a thickness of 0.5 nm or less. 2 / g to 50m 2 / g BET specific surface area.

[0058] As described above, the lithium transition metal oxide according to the present invention may have a grain size of 50 nm to 4000 nm, preferably 50 nm to 2000 nm, and the lithium transition metal oxide may be in the form of secondary particles aggregated from primary particles, or the lithium transition metal oxide may be in the form of a single particle.

[0059] When the lithium transition metal oxide is in the form of a single particle, the carbon coating can be coated on the surface of the lithium transition metal oxide in the form of a single particle with uniform thickness and shape. In addition, when the lithium transition metal oxide is in the form of secondary particles formed by aggregation of primary particles, the carbon coating can be uniformly formed on the surface of the primary particles of the lithium transition metal oxide and the surface of its secondary particles.

[0060] Preferably, the BET specific surface area of ​​the positive electrode active material according to the present invention is 0.5 m 2 / g to 50m 2 / g, preferably 2m 2 / g to 20m 2 / g, more preferably 3m 2 / g to 10m 2 When the BET specific surface area is within the above range, a change in the specific surface area due to the formation of the carbon coating layer is minimized, so that a side reaction between the positive electrode active material and the electrolyte can be suppressed.

[0061] In addition, the powder conductivity of the positive electrode active material according to the present invention is 3.7×10 -3 S / cm to 10.0×10 -3 S / cm, preferably 4.5×10 -3 S / cm to 10.0×10 -3S / cm, the powder conductivity is measured after rolling the positive electrode active material by applying a force of 0.1 kN to 20 kN, preferably 0.5 kN to 10 kN, and most preferably 20 kN. As described above, since the conductivity of the positive electrode active material itself is greatly increased due to the formation of a carbon coating on the surface, when the positive electrode active material is applied to a battery, the electrochemical properties of the battery such as input and output characteristics, life characteristics, etc. can be improved.

[0062] positive electrode

[0063] Furthermore, the present invention provides a positive electrode for a lithium secondary battery, the positive electrode comprising the positive electrode active material produced by the above method.

[0064] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and including the positive electrode active material.

[0065] There is no particular limitation on the positive electrode collector as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and fine concavoconvexities can be formed on the surface of the collector to improve the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0066] The positive electrode active material layer may include a conductive material and a binder as well as a positive electrode active material.

[0067] At this time, the positive electrode active material may be contained in an amount of 80 wt % to 99 wt %, more specifically 85 wt % to 98 wt % relative to the total weight of the positive electrode active material layer. When included within the above content range, the positive electrode active material may exhibit excellent capacity characteristics.

[0068] At this time, the conductive material is used to give the electrode conductivity, and any conductive material can be used without particular limitation as long as it has electronic conductivity and does not cause chemical changes in the battery to be constructed. Specific examples of conductive materials may include: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 1% to 30% by weight relative to the total weight of the positive electrode active material layer.

[0069] The binder is used to improve the bonding between the positive active material particles and the adhesion between the positive active material and the collector. Specific examples of the binder may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used. Relative to the total weight of the positive active material layer, the content of the binder may be 1% to 30% by weight.

[0070] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a conventional method for preparing a positive electrode. Specifically, a positive electrode mixture prepared by dissolving or dispersing the above-mentioned positive electrode active material and a selective binder and a conductive material in a solvent is coated on a positive electrode collector, and then dried and rolled to prepare a positive electrode. At this time, the type and content of the positive electrode active material, the binder and the conductive material are as described above.

[0071] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc. Any one thereof or a mixture of two or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, if the solvent can dissolve and disperse the positive electrode active material, the binder and the conductive material, and thereafter has a viscosity that can show excellent thickness uniformity during coating for manufacturing the positive electrode, the amount of the solvent is sufficient.

[0072] In addition, as another method, the positive electrode may be prepared by casting the positive electrode mixture on a separate support and then laminating a film peeled off from the support on a positive electrode collector.

[0073] Lithium secondary battery

[0074] In addition, the present invention can prepare an electrochemical device comprising the positive electrode, which can be specifically a battery, a capacitor, etc., and more specifically a lithium secondary battery.

[0075] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode arranged facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. The positive electrode is the same as described above, so its detailed description will be omitted. Hereinafter, only the remaining components will be described in detail.

[0076] In addition, the lithium secondary battery may further selectively include: a battery case for accommodating an electrode assembly consisting of a positive electrode, a negative electrode, and a separator; and a sealing member for sealing the battery case.

[0077] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0078] There is no particular restriction on the negative electrode collector as long as it has high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. can be used. In addition, the thickness of the negative electrode collector can generally be 3μm to 500μm, and as in the case of the positive electrode collector, fine concavoconvexity can be formed on the surface of the negative electrode collector to improve the adhesion of the negative electrode active material. For example, the negative electrode collector can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric body.

[0079] The negative electrode active material layer selectively contains a binder and a conductive material in addition to the negative electrode active material.

[0080] Compounds that can reversibly intercalate and deintercalate lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials may include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi)metallic materials that form alloys with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; (semi)metallic oxides that can be doped and undoped with lithium such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a (semi)metallic material and a carbonaceous material such as a Si-C composite material or a Sn-C composite material, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon, etc. can all be used as carbon materials. Representative examples of low-crystalline carbon may include soft carbon and hard carbon, and representative examples of high-crystalline carbon may include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature sintered carbon such as coke derived from petroleum or coal tar pitch.

[0081] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % relative to the total weight of the negative electrode active material layer.

[0082] The binder is a component that helps the bonding between the conductive material, the active material and the current collector, and is generally added in an amount of 0.1% to 10% by weight relative to the total weight of the negative electrode active material layer. Examples of binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0083] The conductive material is a component for further improving the conductivity of the negative electrode active material, and the amount added may be 10% by weight or less, preferably 5% by weight or less, relative to the total weight of the negative electrode active material layer. There is no particular limitation on the conductive material, as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives, etc. may be used.

[0084] For example, the negative electrode active material layer can be prepared by coating a negative electrode mixture material prepared by dissolving or dispersing a negative electrode active material and a selective binder and a conductive material in a solvent on a negative electrode collector and then drying. Alternatively, the negative electrode active material layer can be prepared by casting the negative electrode mixture material on a separate carrier and then laminating the film peeled off from the carrier on the negative electrode collector.

[0085] On the other hand, in lithium secondary batteries, the separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in lithium secondary batteries. In particular, a separator having a high moisture retention capacity for electrolytes and low resistance to the movement of electrolyte ions is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared using polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers; or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed by high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a coated separator having a single-layer or multilayer structure can be selectively used.

[0086] In addition, the electrolyte used in the present invention can be all organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used in the manufacture of lithium secondary batteries, but is not limited thereto.

[0087] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0088] Any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate or propylene carbonate) and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred, which can improve the charge / discharge performance of the battery.

[0089] Any compound can be used as the lithium salt without particular limitation, as long as it can provide the lithium ions used in the lithium secondary battery. Specifically, the following substances can be used as lithium salts: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. The lithium salt can be used in a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and the lithium ions can be efficiently moved.

[0090] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc. At this time, the content of the additive may be 0.1 to 5 parts by weight relative to 100 parts by weight of the total weight of the electrolyte.

[0091] The lithium secondary battery containing the positive electrode active material according to the present invention as described above stably exhibits excellent discharge capacity, output characteristics and life characteristics, and can thus be used in: portable devices such as mobile phones, notebook computers and digital cameras; and can be used in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0092] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit battery, and a battery pack including the battery module.

[0093] The battery module or the battery pack can be used as a power source for one or more medium-to-large devices, such as: power tools; electric vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV); or power storage systems.

[0094] The outer shape of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, or the like.

[0095] The lithium secondary battery according to the present invention can be used in a battery cell used as a power source for small devices, and can also be preferably used as a unit cell of a medium or large battery module including a plurality of battery cells.

[0096] Preferred Implementation

[0097] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, embodiments according to the present invention may be modified into other various forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided to more fully describe the present invention to those skilled in the art.

[0098] Example

[0099] Example 1

[0100] Will be made of LiNi 0.6 CO 0.2 Mn 0.2 The lithium transition metal oxide represented by O2 and the hollow structured carbon black having the specifications of Table 1 below were introduced into a paint shaker (1400Al classic stirrer, Red Devil Co., Ltd), and then mixed for 60 minutes so that the carbon black was 1 wt % relative to 500 g of the lithium transition metal oxide, so that the transition metal oxide and the hollow structured carbon black were uniformly dispersed.

[0101] The above mixture was introduced into a mechanical fusion device (nobilta, Hosokawa Micron Co., Ltd), and then processed at 3000 rpm for 10 minutes to produce a positive electrode active material in which a carbon coating layer with a thickness of 200 nm was formed on the lithium transition metal oxide.

[0102] Example 2

[0103] A positive electrode active material in which a carbon coating layer having a thickness of 250 nm was formed on the lithium transition metal oxide was manufactured in the same manner as in Example 1, except that the mixing was performed in such a manner that the carbon black was 1 wt % relative to 200 g of the lithium transition metal oxide.

[0104] Example 3

[0105] A positive electrode active material in which a carbon coating layer having a thickness of 250 nm was formed on the lithium transition metal oxide was manufactured in the same manner as in Example 1, except that the mixing was performed in such a manner that the carbon black was 1 wt % relative to 100 g of the lithium transition metal oxide.

[0106] Example 4

[0107] A positive electrode active material in which a carbon coating layer having a thickness of 250 nm was formed on the lithium transition metal oxide was manufactured in the same manner as in Example 1, except that the mixing was performed in such a manner that the carbon black was 1 wt % relative to 50 g of the lithium transition metal oxide.

[0108] Comparative Example 1

[0109] Will be made of LiNi 0.6 CO 0.2 Mn 0.2The lithium transition metal oxide represented by O2 and the hollow structure carbon black having the specifications of the following table 1 were introduced into a paint stirrer (1400Al classic stirrer, Red Devil Co., Ltd), and then mixed for 60 minutes so that the carbon black was 1% by weight relative to 500g of the lithium transition metal oxide, so that the transition metal oxide and the hollow structure carbon black were uniformly dispersed. As a result, a mixture in which the lithium transition metal oxide and the carbon black were uniformly mixed was produced, which was used as a positive electrode active material.

[0110] Comparative Example 2

[0111] A lithium transition metal oxide having no carbon coating layer formed thereon is used as a positive electrode active material.

[0112] Comparative Example 3

[0113] A mixture in a form in which aggregated carbon black was adsorbed on the surface of the lithium transition metal oxide was manufactured in the same manner as in Example 2, except that carbon black having the specifications of the following Table 1 was used.

[0114] Comparative Example 4

[0115] A mixture in a form in which aggregated carbon black was adsorbed on the surface of the lithium transition metal oxide was manufactured in the same manner as in Example 1, except that carbon black having the specifications of the following Table 1 was used.

[0116] Comparative Example 5

[0117] A mixture in which carbon black and a lithium transition metal oxide were uniformly mixed was produced in the same manner as in Comparative Example 1 except that carbon black having the specifications of the following Table 1 was used, and the mixture was used as a positive electrode active material.

[0118] Comparative Example 6

[0119] A positive electrode active material in which a carbon coating layer having a thickness of 350 nm was formed on a lithium transition metal oxide was manufactured in the same manner as in Example 1, except that carbon black having the specifications of the following Table 1 was used.

[0120] [Table 1]

[0121]

[0122] Experimental Example 1

[0123] (1) Identification of the surface properties of positive electrode active materials

[0124] The surface properties of the various positive electrode active materials in Example 1 and Comparative Examples 1, 2, 4 and 6 were confirmed and shown in Figures 3 to 6 middle.

[0125] first, Figure 3 : is a SEM image showing the surface of (a) the positive electrode active material of Comparative Example 2, (b) the positive electrode active material of Comparative Example 1, and (c) the positive electrode active material of Example 1. At this time, Comparative Example 2 ( Figure 3 (a)) is a positive electrode active material having no coating formed on its surface, and compared with Comparative Example 2, in the case of the positive electrode active material of Example 1, it was confirmed that the carbon-based coating was uniformly coated on the surface of the lithium transition metal oxide (in Figure 3 On the other hand, in the case of the positive electrode active material produced in Comparative Example 1, it can be confirmed that the residue of the carbon particles exists in the form of being attached to the surface thereof.

[0126] on the other hand, Figure 4 : are SEM images showing the surfaces of (a) the positive electrode active material of Comparative Example 2, (b) the positive electrode active material of Comparative Example 4, and (c) the positive electrode active material of Example 1. Figure 4 As shown in (b), when densely structured carbon black is applied, it is confirmed that even when the carbon coating is formed by mechanical fusion, the carbon particles are not uniformly coated on the surface of the particles, but are attached to the boundaries of the primary particles in an aggregated form.

[0127] also, Figure 5 is a SEM image of the surface of the positive electrode active material of Example 1, Figure 6 is a SEM image of the surface of the positive electrode active material of Comparative Example 6. Figure 5 As shown in FIG. 1 , when the carbon black satisfying all the requirements of the present invention in terms of shape, specific surface area, degree of graphitization and DBP oil absorption is used, it is confirmed that the carbon coating is uniformly formed on the surface. Figure 6 As shown, when the shape, specific surface area, degree of graphitization or DBP oil absorption of the present invention are not satisfied, it is confirmed that the carbon coating layer is not uniformly formed ( Figure 6 (the white part of the

[0128] (2) Powder conductivity of positive electrode active material (S / cm)

[0129] 5 g of the positive electrode active material prepared in Examples 1 to 4 and Comparative Examples 1 to 6, respectively, was placed in a holder and then rolled by applying a force of 30 kN thereto. The powder conductivity of each positive electrode active material was measured using 4 detection ring electrodes for powder only (Mitsubishi Chemical, powder resistance system (MCP = PD51)), and the results are shown in Table 2 below.

[0130] (3) BET specific surface area

[0131] The specific surface area of ​​each positive electrode active material of Examples 1 to 4 and Comparative Examples 1 to 6 was measured by the BET method. Specifically, the specific surface area was calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using Belsorp-mino II of BEL Japan Co., Ltd., and the results are shown in Table 2.

[0132] [Table 2]

[0133] Conductivity (S / cm) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 <![CDATA[8.21×10 -3 ]]> 5.98 Example 2 <![CDATA[6.96×10 -3 ]]> 5.89 Example 3 <![CDATA[5.73×10 -3 ]]> 4.58 Example 4 <![CDATA[4.82×10 -3 ]]> 3.42 Comparative Example 1 <![CDATA[3.64×10 -3 ]]> 2.56 Comparative Example 2 <![CDATA[2.17×10 -3 ]]> 0.26 Comparative Example 3 <![CDATA[2.15×10 -3 ]]> 1.58 Comparative Example 4 <![CDATA[2.35×10 -3 ]]> 1.66 Comparative Example 5 <![CDATA[2.44×10 -3 ]]> 1.43 Comparative Example 6 <![CDATA[5.54×10 -3 ]]> 3.97

[0134] As shown in Table 2 above, the positive electrode active materials manufactured in Examples 1 to 5 had improved positive electrode active material powder conductivity compared to Comparative Examples 1 to 5.

[0135] Experimental Example 2

[0136] Lithium secondary batteries were prepared using the various cathode active materials manufactured in Examples 1 to 4 and Comparative Examples 1 to 6, and the capacities of the various lithium secondary batteries including the various cathode active materials of Examples 1 to 4 and Comparative Examples 1 to 6 were evaluated.

[0137] Specifically, various positive active materials, carbon conductive materials and polyvinylidene fluoride (PVdF) prepared in Examples 1 to 4 and Comparative Examples 1 and 6 were mixed in an N-methylpyrrolidone (NMP) solvent at a weight ratio of 97.5:1.0:1.5 to prepare positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 130°C, and then rolled to prepare a positive electrode.

[0138] On the other hand, artificial graphite used as negative electrode active materials, carbon black conductive material, and styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) as binders were mixed in distilled water at a weight ratio of 96.4:0.5:2.3:1.1 to prepare negative electrode active material slurry. The negative electrode active material slurry was coated on a copper current collector having a thickness of 20 μm, dried, and then rolled to prepare a negative electrode.

[0139] A polyethylene separator having a thickness of 15 μm was inserted between the positive electrode and the negative electrode manufactured above to prepare an electrode assembly, and the electrode assembly was placed in a battery shell. Thereafter, an electrolyte was injected into the shell to manufacture a lithium secondary battery. At this time, as an electrolyte, an electrolyte prepared by dissolving 1M LiPF6 in a mixed organic solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 was used to prepare various lithium secondary batteries according to Examples 1 to 4 and Comparative Examples 1 to 6.

[0140] Next, each lithium secondary battery manufactured in Examples 1 to 4 and Comparative Examples 1 to 6 was charged to 4.25 V at 25° C. with a constant current of 0.2 C and a cutoff value of 0.05 C. Next, each lithium secondary battery was discharged to 2.5 V at a constant current of 0.2 C to determine the initial charge and discharge capacity.

[0141] Thereafter, the battery was charged to 4.25 V at a constant current of 0.2 C under the condition of 0.05 C cutoff, and then discharged at a constant current of 2.0 C until it reached 2.5 V. The above charge / discharge behavior was set as 1 cycle, and the cycle was repeated 2 times. Thereafter, the capacity characteristics at 2.0 C relative to the 0.2 C discharge capacity of various lithium secondary batteries according to Examples 1 to 4 and Comparative Examples 1 to 6 were measured, and the results are shown in Table 3 below.

[0142] [Table 3]

[0143] 2.0C discharge capacity ratio (%, based on 0.2C discharge capacity) Example 1 92.7 Example 2 90.6 Example 3 88.9 Example 4 81.3 Comparative Example 1 80.1 Comparative Example 2 81.5 Comparative Example 3 75.3 Comparative Example 4 74.9 Comparative Example 5 73.6 Comparative Example 6 82.8

[0144] As shown in Table 3 above, it was confirmed that the capacity characteristics of the secondary batteries of Examples 1 to 4 were superior to those of Comparative Examples 1 to 5. On the other hand, the capacity characteristics of the secondary battery of Comparative Example 6 were significantly inferior to those of Example 1 in which the same weight of lithium transition metal oxide was used.

Claims

1. A method for manufacturing a positive electrode active material, the method comprising: Mixing a lithium transition metal oxide and a hollow-structured carbon material to form a mixture; as well as The mixture is mechanically treated so that the carbonaceous material is crushed due to structural collapse and a carbon coating is formed on the surface of the lithium transition metal oxide. The hollow carbon material is in the form of a chain and has a diameter of 500 m 2 / g or more, a specific surface area of ​​1.0 or more, and a degree of graphitization I D / I G and DBP oil absorption of more than 300mL / 100g. 2 . The method according to claim 1 , wherein a mixing amount of the carbon-based material is 0.1 parts by weight to 1.5 parts by weight relative to 100 parts by weight of the lithium transition metal oxide.

3. The method of claim 1, wherein mechanically treating the mixture is performed by mechanofusion. The method according to claim 1 , wherein the carbon-based material is in the form of secondary particles formed by aggregation of primary particles. The method according to claim 4 , wherein the size of the primary particles of the carbon-based material is 50 nm or less.

6. The method according to claim 1, wherein the carbon-based material has a 2 / g to 2500m 2 / g specific surface area.

7. The method according to claim 1, wherein the carbon-based material has a graphitization degree I of 1.0 to 2.

0. D / I G . The method according to claim 1 , wherein the carbon-based material has a DBP oil absorption of 300 mL / 100 g to 2000 mL / 100 g.

9. A positive electrode active material manufactured by the method of claim 1, the positive electrode active material comprising: Lithium transition metal oxides; and forming a carbon coating on the surface of the lithium transition metal oxide, wherein the carbon coating is formed on the surface of the lithium transition metal oxide, and The carbon coating has a thickness of 500 nm or less, and the positive electrode active material has a thickness of 0.5 nm or less. 2 / g to 50m 2 / g BET specific surface area.

10. The positive electrode active material according to claim 9, wherein the positive electrode active material has a -3 S / cm to 10.0×10 -3 Powder conductivity in S / cm, The powder conductivity is measured after rolling the positive electrode active material by applying a force of 0.1 kN to 20 kN thereto. 11 . A positive electrode for a lithium secondary battery, comprising the positive electrode active material according to claim 9 . 12 . A lithium secondary battery, comprising the positive electrode for a lithium secondary battery according to claim 11 .

Citation Information

Patent Citations

  • Variable muffler cutter for a vehicle

    KR1020200011338A

  • Electrode for lithium secondary battery and lithium secondary battery using it

    JP2003308845A

  • Positive electrode active material and method of manufacturing the same, and rechargeable lithium battery including the positive electrode active material

    KR101666871B1

  • Surface-treated positive active material, method for surface-treating positive active material, and electrochemical devices including the same surface-treated positive active material

    KR1020180071106A

  • Active materials for a secondary cell, a method for making the same, positive electrodes for a secondary cell comprising the active material, and a non-aqueous electrolytic secondary cell

    US5789114A